The significance of number of design variables on optimal shell solutions. - Petchsasithon, Arthit (Asean Engineering Journal)
This paper describes the significance of the effect of the number of design variables on the optimal solution. An 18 node hexahedral shell is adopted as the basic element formulation with the inclusion of proposed methodologies to alleviate various locking phenomena. An automatic mesh generation scheme using Bezier surface method is employed to avoid re-meshing structures after each iteration of optimization process. Various benchmarks are performed to demonstrate the dependence of the optimal solutions on the number of design variables.